2022
DOI: 10.3390/ijms232314632
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Extracellular Vesicles in Aging and Age-Related Diseases

Abstract: Aging is associated with an alteration of intercellular communication. These changes in the extracellular environment contribute to the aging phenotype and have been linked to different aging-related diseases. Extracellular vesicles (EVs) are factors that mediate the transmission of signaling molecules between cells. In the aging field, these EVs have been shown to regulate important aging processes, such as oxidative stress or senescence, both in vivo and in vitro. EVs from healthy cells, particularly those c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 170 publications
0
7
0
Order By: Relevance
“…It has been well-documented that EVs are involved in aging processes through regulating multiple biogenesis pathways, such as cellular senescence, inflammation, tissue regeneration, oxidative stress, metabolism and autophagy ( 1 , 7 , 19 , 40 , 41 ). We have observed age-associated declines of multiple immune cell-related EV subpopulations in healthy humans and mice, consistent with an immunosenescence phenotype in healthy aging that is reflected in EV subpopulations ( 1 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented that EVs are involved in aging processes through regulating multiple biogenesis pathways, such as cellular senescence, inflammation, tissue regeneration, oxidative stress, metabolism and autophagy ( 1 , 7 , 19 , 40 , 41 ). We have observed age-associated declines of multiple immune cell-related EV subpopulations in healthy humans and mice, consistent with an immunosenescence phenotype in healthy aging that is reflected in EV subpopulations ( 1 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical investigations showed that exosomes may have a therapeutic role in aging and other age-related diseases [99]. Cellular aging is due to various biological changes including, epigenetic alteration, genomic instability, senescence, oxidative stress, mitochondrial decline, and dysregulation of intracellular communication [100].…”
Section: Clinical Applicability Of Exosomes In Photoaging: Current St...mentioning
confidence: 99%
“…Some studies have demonstrated the therapeutic potential of exosome in preclinical models of age-related diseases such as Alzheimer's, Type 2 diabetes (T2DM), osteoarthritis, chronic kidney disease, etc. [99].…”
Section: Clinical Applicability Of Exosomes In Photoaging: Current St...mentioning
confidence: 99%
“…The reason is that EVs are released by all human cells and are ubiquitous conveyors of intercellular messages and can function as intercellular mediators because of their selective cargoes, such as specific miRNAs, proteins, and lipids [ 94 , 95 ]. They contain a wealth of biomarkers which could be used to monitor the status of some pathologies and clinical conditions [ 96 ]. The exact EV contents could be advantageous in using EVs as a biomarker in developing diseases.…”
Section: Extracellular Vesicles As Biomarkers In Aging and Age-associ...mentioning
confidence: 99%